Subjective Assessment of Appetite at High Altitude and Factors Associated with Decreased Appetite - Zubair, Usama Bin; Saif, Anas Bin; Mumtaz, Humza; Khan, Nazir A (Journal of Pakistan Psychiatric Society, 2016)
Abstract